THE ANALYSIS OF STUDENTS’ DIFFICULTIES IN WRITING RECOUNT TEXT - Sartika, Dewi; Khairinisaak, Khairinisaak; Asmara, Rekha (Journal of English Education Program, 2022)
The purpose of this research was to explain difficulties faced by the eighth graders of SMP Bait Qur'an in writing a recount text. Descriptive qualitative was used to investigate this research. To obtain the data, a written test and a questionnaire were applied. To analyze the obtained data, data reducing, data displayed, content analysis, and drawing a conclusion were applied. Then the data were analyzed using percentage analysis. The test results showed that most students had poor ability in writing a recount text. It could be seen that 12 students (54.54%) were very poor in writing content of the recount text, 15 students (68.18%) were very poor in the organization of the recount text, 12 students (54.54%) were very poor in the vocabulary of the recount text, 19 students (86.37%) were very poor in the grammar of the recount text, and 16 students (72.72%) were very poor in the mechanic of the recount text. Most students had difficulties understanding grammar use in a recount text. It happened because they were lack of knowledge about the recount text itself and less practice writing a recount text.